Consumption of Pasteurized Whole Milk Challenges in Padang, Indonesia: Insights from Consumers and Business Perspectives - Ratni, Eli; Lendrawati (Andalasian Livestock, 2024)
This study investigates the challenges and opportunities surrounding the decline in local pasteurized whole dairy milk consumption in Indonesia, focusing on West Sumatra. Despite potential health benefits, factors such as limited availability, storage challenges, and concerns about taste and product quality have hindered the adoption of whole milk as a mixing ingredient in contemporary beverages. Through a survey of beverage outlets in Padang City and analyzing consumer preferences, this research identifies critical barriers businesses face and proposes interventions to address them. These interventions include improving milk accessibility, providing business educational programs, promoting taste and quality benefits, supporting recipe development, conducting market research, and collaborating with suppliers. By addressing these challenges, businesses can expand consumer choice, stimulate demand, and drive growth in the whole milk-based beverage market, ultimately benefiting local dairy farmers and public health in Indonesia.